Product-moment correlation limitations and the appropriateness of confirmatory analysis to verify internal structure of a construct: A critical review - Bilson Simamora (Jurnal Ekonomi Perusahaan, 2025)
Product-moment correlation is often used to verify the internal structure of a construct. Despite its widespread use among undergraduate and graduate students, and its inclusion in nationally distributed textbooks, the author argues that this technique is fundamentally flawed. This study aims to explain the shortcomings of product-moment correlation. This study found that Confirmatory factor analysis (CFA) is the appropriate technic for that purpose because use only common variance, latent variable score is obtained only from its verified indicators and the researcher can check the ability of each indicator ability to explain its latent variable.